Geração automática de casos de teste para sistemas baseados em agentes móveis. - FIGUEIREDO, André Luiz Lima de. (2005)
Submitted by Johnny Rodrigues (johnnyrodrigues@ufcg.edu.br) on 2018-09-18T16:07:15Z No. of bitstreams: 1 ANDRÉ LUIZ LIMA DE FIGUEIREDO - DISSERTAÇÃO PPGCC 2005..pdf: 9317771 bytes, checksum: ca97057cbb4f85db739568ea619fd2c4 (MD5)